2006
DOI: 10.1002/jcla.20092
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Chlamydia trachomatis infection

Abstract: Important progress in the diagnosis of Chlamydia trachomatis (C. trachomatis) includes the development of nucleic acid amplification techniques such as polymerase chain reaction (PCR) and ligase chain reaction (LCR). Commercial kits are available, but they are costly, sporadic in availability, must be imported, and are economically beyond the reach of common people. To overcome this limitation, most research laboratories have standardized their in‐house‐developed PCR methods for diagnosing this infection. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 9 publications
1
14
0
Order By: Relevance
“…The gynecologist read the vaginal pH after removing the speculum from the vagina to avoid interpersonal variation. Swab collected from the endocervix was used for C. trachomatis detection by polymerase chain reaction following the indigenously standardized technique (20). Statistical analysis was done using Epi Info version 6 package with Yates correction of w 2 value.…”
Section: Methodsmentioning
confidence: 99%
“…The gynecologist read the vaginal pH after removing the speculum from the vagina to avoid interpersonal variation. Swab collected from the endocervix was used for C. trachomatis detection by polymerase chain reaction following the indigenously standardized technique (20). Statistical analysis was done using Epi Info version 6 package with Yates correction of w 2 value.…”
Section: Methodsmentioning
confidence: 99%
“…PCR was performed on extracted DNA using a primer pair selected from the conserved region of the Major Outer Membrane Protein (MOMP) gene of C. trachomatis 15 following a standardized PCR program. 16 This primer pair amplifies an 180bp DNA fragment, which is common to all serotypes of C. trachomatis. The amplified 180bp PCR products were immediately frozen for further analysis or electrophoresis was carried out on 2% agarose gel containing Ethidium bromide and observed under a UV transilluminator and the results were documented.…”
Section: Subjectsmentioning
confidence: 99%
“…On the other hand, some authors reported that sensitivity of ELISA was 50 and 58%, respectively and the specificity was 100% by both studies (Malik et al, 2006;Mania-Pramanik et al, 2006). However, it was stated that in low prevalence populations the positive predictive value decreases rapidly with specificity which is a mathematical relationship (Dierksheide, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…The sequences of these oligonucleotide primers from 5' to 3' are as follows: Sense: 5' GCC GCT TTG AGT TCT GCT TCC 3'. Antisense: 5' GTC GAA AAC AAA GTC ACC ATA GTA 3' (Mania-Pramanik et al, 2006). PCR was done in a total volume of 50 µL.…”
Section: Pcrmentioning
confidence: 99%